Pengembangan Modul Ajar Berbasis Pembelajaran Berdiferensiasi Pada Materi â€œMenggunakan Dataâ€ - Titin Suryani; Syarifah Fadillah Al Hadad; Jamilah Jamilah (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2023)
This research is by using research and development (RnD) method. The model used is the 3-D model approach or development, which stands for Define, Design, and Development. The purpose of this research is to develop teaching modules based on differentiated learning on material using data. The research subjects were 20 students of class VII SMP Assalam Pontianak Islamic Boarding School. Data analysis techniques used are interviews, indirect communication techniques, and measurement scatter hitam techniques. The instruments used in this study were test sheets for learning outcomes, validation sheets, and response questionnaires. Differentiation-based teaching modules have media and material validity levels of 90.26% and 83.58%, respectively, in the